BEDAS POLICIES (RISING, EDUCATION, DYNAMIC, RELIGION, AND PROSPEROUS) IN DISDUKCAPIL, BANDUNG DISTRICT - Rosmery Elsye Elsye (Universitas Padjadjaran, 2023)
This study aims to make a visual representation of how the Department of Occupation and Civil Records (Disdukcapil) Government of Bandung implemented public policy “BEDAS” (Bangkit, Edukasi, Dinamise, Agamis, and Sejahtera). This research belongs to qualitative research because it uses primary and secondary materials. The researchers in this study used vital actors who managed population registration services and samples. Essential personnel of this study includes the head of UPT, the head of Capil, and the head of DukCapil of Bandung. Secondary and primary data are used to compile the results of this research. Data collection techniques include open conversation, careful observation, and comprehensive documentation. (Pustaka). Data analysis is carried out descriptively and explained realistically; the research subject is the entire staff of Disdukcapil Districts of Bandung, with a total sample of 20 people selected randomly. And we used random samples taken from local government officials, religious figures, community members, and business owners in the region. (“Subjek”). The research findings showed that implementing the BEDAS policy by the Disdukcapil Districts of Bandung succeeded in carrying out various activities to help local communities access the administrative services they need. Based on the findings of this research, it can be concluded that the policy of BEDAS in the Disdukcapil district of Bandung is running smoothly and has improved the quality of services provided to the community.